> 数学 >
已知a>2,求证:log(a-1)a>loga(a+1)
人气:167 ℃ 时间:2020-04-18 19:08:11
解答
证明(法一):∵log(a−1)a−loga(a+1)=
1
loga(a−1)
−loga(a+1)

=
1−(loga(a−1))•(loga(a+1))
loga(a−1)

因为a>2,所以,loga(a-1)>0,loga(a+1)>0,
所以,loga(a-1)•loga(a+1)[
loga(a−1)+loga(a+1)
2
]
2

=
[loga(a2−1)]2
4
[logaa2]2
4
=1

所以,log(a-1)a-loga(a+1)>0,命题得证.
证明2:因为a>2,所以,loga(a-1)>0,loga(a+1)>0,
所以,
log(a−1)a
loga(a+1)
1
loga(a−1)
loga(a−1)
1
(loga(a−1))•(loga(a+1))

由法1可知:loga(a-1)•loga(a+1)[
loga(a−1)+loga(a+1)
2
]
2

=
[loga(a2−1)]2
4
[logaa2]2
4
=1

1
loga(a−1)•loga(a+1)
>1.
故命题得证
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版